Hepatitis B virus reactivation in patients with rheumatoid arthritis: A single-center study. Issue 5 (3rd September 2018) - Matsuzaki, Toshihisa; Eguchi, Katsumi; Nagao, Natsumi; Tsuji, Sousuke; Aramaki, Toshiyuki; Terada, Kaoru; Iwatsu, Shinichi; Tokimura, Ikuko; Kamo, Yasuhiro; Oda, Hidetoshi; Kinoshita, Noboru; Miyaaki, Hisamitsu; et al.
Abstract: Objectives: This study aimed to investigate the frequency of hepatitis B virus (HBV) reactivation in patients with rheumatoid arthritis (RA) and to verify the guidelines relating to HBV reactivation in Japan. Methods: We retrospectively investigated 1351 RA patients who were treated with antirheumatic drugs at our hospital. Results: Fifty patients (3.7%; 50/1351) were determined to be HBV carriers and 360 patients (26.7%; 360/1351) had resolved infections. HBV reactivation occurred in six cases (1.7%: 6/360) with resolved infections, of whom, two cases (0.6%; 2/360) developed de novo HBV infections. Eleven of the patients who were HBV carriers received a nucleoside analogue (NA) prophylactically. In all of the cases, the HBV-DNA levels became undetectable and the patients' liver function normalized. Sixteen patients, who had lower titers of the HBV surface antigen and undetectable HBV-DNA levels, did not show HBV reactivation in the absence of NA therapy. Conclusions: The results from this study suggest that HBV reactivation might not be so frequent among RA patients, and that reliable indicators for prescribing a NA should be clarified for RA patients.